2015
DOI: 10.5511/plantbiotechnology.14.1122a
|View full text |Cite
|
Sign up to set email alerts
|

&#x3b1;-Amylase from Mon Thong durian (<i>Durio zibethinus</i> Murr. cv. Mon Thong)-nucleotide sequence analysis, cloning and expression

Abstract: Amylase is hypothesized to involve in the initiation of intracellular starch granule digestion in the plastids of ripening durians. A putative α-amylase from Mon Thong durian (Durio zibethinus Murr. cv. Mon Thong; DzAmy3) was successfully isolated and its gene contain a 2,679 base pair open reading frame, which encodes 892 amino acids with a calculated molecular mass of 93.7 kDa and an isoelectric point of 5.77. The DzAmy3 contains starch binding domain with a putative plastid transit peptide and α-amylase lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The samples were prepared under non-reducing conditions and separated on 13% polyacrylamide gels containing 0.1% w/v soluble starch (Posoongnoen et al 2015). The gel was washed with 1% v/v triton X-100 to remove SDS and then incubated with 0.2% w/v starch in 50 mM sodium acetate buffer (pH 5.5) for 6 h at 37°C.…”
Section: Zymographic Methodsmentioning
confidence: 99%
“…The samples were prepared under non-reducing conditions and separated on 13% polyacrylamide gels containing 0.1% w/v soluble starch (Posoongnoen et al 2015). The gel was washed with 1% v/v triton X-100 to remove SDS and then incubated with 0.2% w/v starch in 50 mM sodium acetate buffer (pH 5.5) for 6 h at 37°C.…”
Section: Zymographic Methodsmentioning
confidence: 99%
“…However, the difference between VD and IE in this region does not affect the mechanistic properties. In this study, nearly all critical domains and region of MiAmy are found, which are as follows: (1) the two consecutive tryptophan residues for starch-granule binding, which correspond to W469 and W470 (Tangphatsornruang et al, 2005), (2) the conserved residues thought to be the Ca 2+ binding site, (3) the residues involved in hydrogen bonding with the α-amylase inhibitor acarbose, (4) Tyr 570 in domain C, corresponding to Tyr807 of DzAmyF3, which was suggested to be a sugar tongs surface binding site (Posoongnoen et al, 2015). Thus, the MiAmy α-amylase gene is predicted to be valuable for further studies, including its modification.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic studies are essential in understanding multiple pathways, gene expression patterns, and secondary metabolites biosynthesis in developing fruits or tissues of interest. Several studies on gene expression patterns and gene expression profiles at the molecular level in Durian varieties have been reported ( Nyffeler and Baum, 2000 ; Ruwaida, 2009 ; Vanijajiva, 2011 , 2012 ; Hariyati et al, 2013 ; Santoso and Saleh, 2013 ; Posoongnoen et al, 2015 ; Teh et al, 2017 ; Husin et al, 2018 ). In transcriptomics of Durian, Musang King var., ripening-related gene sets included genes regulated by the MADS-BOX transcription factor family 29, SEPALLATA transcription factor family, and ethylene-related genes such as ACS (aminocyclopropane-1-carboxylic acid synthase), a key ethylene-production enzyme, are involved in ripening ( Teh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%